Preference for green outdoor environment over indoor spaces by cardiac survivors with walking as a rehabilitative activity - Amat, Nur Syakira Amira (2017)
Heart disease is the number one killer in Malaysia and alarmingly, the numbers of cardiac survivors are increasing throughout the year. Currently, the cardiac rehabilitation activity is mostly being carried out in the Department of Rehabilitation located inside a building rather than utilising the green outdoor environments which can be found within the hospitals’ compounds. Furthermore, the green outdoor environments are hardly meet the requirements or preferences to be utilized for cardiac rehabilitation purposed and there is still a lack of study on the use of green outdoor environments for cardiac rehabilitation. The main purpose of this study is to identify if the Green Outdoor Environment (GOE) is influencing the cardiac survivors’ physiological responses that consist of heart rate (bpm) and blood pressure (mmHg) during the cardiac rehabilitation sessions. Therefore, there are few objectives established which are to assess the physiological responses of cardiac survivors during the walking exercise carried out during the outdoor and indoor sessions, to identify the respondents’ preferences for an ideal outdoor setting of green outdoor environments, and to recommend the design of outdoor spaces for cardiac rehabilitation usage at hospitals. This study was carried out at the Medical Rehabilitation Department of Rehabilitation Medicine, Serdang Hospital which provides a rehabilitation treatment program for the cardiac survivors called Cardiac Rehabilitation Program (CRP). Forty cardiac survivors who completed all six-week treatments involved with the outdoor and indoor sessions were chosen as the respondents. The walking exercise was selected as the comparative activities between the outdoor session and indoor session. Walking distance without obstacles represents the outdoor session while walking on the treadmill represents the indoor session. The readings of cardiac survivors’ physiological responses (heart rate and blood pressure) collected from the exercise record during CRP. A questionnaire was given to identify their preferences regarding the ideal outdoor setting of GOE during reassessment session of CRP and the design considerations of green outdoor environments. The preferences were divided into the type of settings, landscape features and leisure activities that can be done outdoor. The results were coded into the Statistical Package for Social Science (SPSS) Version 22 and analysed by using one-way analysis of variance (ANOVA). The results from the findings indicated that outdoor session has influenced the heart rate readings of the cardiac survivors but not in the readings of their blood pressure. However, the readings of heart rate and blood pressure of the cardiac survivors were not influenced by the indoor session. Most of the cardiac survivors preferred to have a more nature-based surrounding for their comfort and as according to them; the setting provided the positive vibes during the outdoor session of rehabilitation. This has shown that an ideal outdoor setting is important for the cardiac rehabilitation as it may have affected the physiological responses of the cardiac survivors in a positive way and the cardiac survivors’ preferences also should be taken into consideration regarding the design of green outdoor environments.